2021
DOI: 10.1155/2021/8815048
|View full text |Cite
|
Sign up to set email alerts
|

Complex Coronary Instent Chronic Total Occlusion Lesions: Oxidative Stress, Inflammation, and Coronary Stent Lengths

Abstract: The oxidative stress and inflammation played the key roles in the development of atherosclerotic coronary plaques. However, the relationships between pro/antioxidant, pro/anti-inflammatory status, and complex coronary instent chronic total occlusion lesions were not clear in the elderly patients with very long stent implantations. We tried to evaluate the roles of pro/antioxidant and pro/anti-inflammatory biomarkers in the diagnosis of complex reocclusion lesions in elderly patients after coronary stenting. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that oxidative damage is associated with inflammation (Mohammed et al, 2021). Oxidative stress also increases the pro‐inflammatory response to induce more severe oxidative stress (Li et al, 2021). IL‐6, IL‐8, and TNF‐α are all pro‐inflammatory biomarkers (Rajandran et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that oxidative damage is associated with inflammation (Mohammed et al, 2021). Oxidative stress also increases the pro‐inflammatory response to induce more severe oxidative stress (Li et al, 2021). IL‐6, IL‐8, and TNF‐α are all pro‐inflammatory biomarkers (Rajandran et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant differences were observed between the studied groups regarding other OS markers including thiol levels, antioxidant enzyme activities, and TAC. Previously, an increase in markers of OS has been observed after coronary stent implantation, suggesting OS as a trigger of a complex chain of events leading to restenosis [ 16 , 17 ]. Limitations of the evaluation of MDA, which showed a higher levels in ISR patients compared to the healthy group, have been discussed; however, the test is very simple, rapid, inexpensive, and relatively reliable [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays a vital role in disease progression and the prognosis of patients, it can not only accelerate the formation of plaque lesions but also promote the progression of complex re-occlusion lesions in elderly patients with very long stent implantations ( 5 , 30 ). C-reactive protein acts as a biomarker of inflammation and a hallmark of acute-phase response, which can strongly reflect the inflammation status of patients.…”
Section: Discussionmentioning
confidence: 99%